Unwrapping IT Project Success in China: Examining the Role of Empowering Leadership, Workforce Agility and Top Management Support in IT Project Success - Shoukat Iqbal Khattak; Muhammad Anwar Khan; Muhammad Iftikhar Ali; Abdul Samad kakar (SAGE Open)
Information technology (IT) projects frequently struggle to fulfill their potential in today’s rapidly evolving technological landscape. Empowering leadership (EL) has emerged as a critical factor for project success; however, the underlying mechanisms of how and why EL is linked to IT project success remain largely unknown. This study aims to fill this gap by investigating the mediating and moderating roles of workforce agility (WA) and top management support (TMS) in the EL-IT project success relationship. Purposive sampling was used to collect data from 328 IT professionals in the main cities of Fujian Province, China. The data were analyzed using SPSS 24 and SmartPLS 3.2.9. The results indicate that EL is positively and significantly related to IT project success and WA, respectively. Consequently, WA has a significant and positive relationship with IT project success. The results also supported the mediating role of WA in the relationship between EL and IT project success. The study also revealed that TMS positively moderated the relationship between EL and WA. Theoretically, this study expands the project management literature by applying self-determination theory (SDT) and conservation of resource (CoR) theory to demonstrate the crucial role of EL in IT project success, particularly in the Chinese context. By focusing on the mediating and moderating effects of WA and TMS, this study provides valuable insights into the complex mechanisms underlying EL’s impact on IT project success.